Synthesis and Characterization of Aryl Alkanoic Acids as Potential Antimicrobial Agents - NAGALAKSHMI, G. (Asian Journal of Chemistry, 2010)
Aryl alkanoic acid moieties are important because of its versatile biological actions. In the present study, aryl alkanoic acids (IIIa-j) have been synthesized by the condensation of 4-aminobenzoic acid (I) with various aromatic halides (IIa-j) in presence of glacial acetic acid. The structures of the newly synthesized compounds were characterized on the basis of elemental analysis, UV, IR and 1H NMR spectral data. The synthesized compounds were screened for their in vitro growth inhibiting activity against different strains of bacteria and fungi viz., Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Candida albicans and Aspergillus niger were compared with the standard antibiotics such as amikacin (30 μg/mL) and fluconazole (100 μg/mL) using well agar diffusion technique. Compounds (IIIa, IIIe, IIIh and IIIi) showed comparable antibacterial activity.